2017
DOI: 10.1021/acs.jpca.7b09394
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Complexes with Five-Membered Heterocycles: Structure, Topology, and Spectroscopic Characterization

Abstract: In a first step toward the rational design of macrocyclic structures optimized for CO capture, we systematically explored the potential of 30 five-membered aromatic heterocycles to establish coordinating complexes with this pollutant. The interactions between the two moieties were studied in several orientations, and the obtained complexes were analyzed in terms of electron density and vibrational fingerprint. The former is an aid to provide an in-depth knowledge of the interaction, whereas the latter should h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 119 publications
(151 reference statements)
0
15
0
Order By: Relevance
“…In previous works, it has been shown that carbon dioxide is able to form complexes with phosphines, 8 11 sulfur dioxide, 12 pyridine derivatives, 13 15 imidazole, 16 18 and other heterocycles. 19 , 20 It has also been proved that CO 2 can form adducts with carbenes 21 27 and frustrated Lewis pairs (FLPs), 28 33 some of them including silicon and germanium as Lewis acid centers. 34 36 …”
Section: Introductionmentioning
confidence: 99%
“…In previous works, it has been shown that carbon dioxide is able to form complexes with phosphines, 8 11 sulfur dioxide, 12 pyridine derivatives, 13 15 imidazole, 16 18 and other heterocycles. 19 , 20 It has also been proved that CO 2 can form adducts with carbenes 21 27 and frustrated Lewis pairs (FLPs), 28 33 some of them including silicon and germanium as Lewis acid centers. 34 36 …”
Section: Introductionmentioning
confidence: 99%
“…Hernández-Marín and Lemus-Santana studied the complexes between CO 2 and imidazole, 2-methylimidazole, benzimidazole and pyrazine using DFT methods [ 31 ]. Finally, Vidal-Vidal, Nieto Faza and Silva López extended studies of π-complexes to those with 1H-pyrrole, 1H-pyrazole, 1H-1,2,3-triazole, 2H-1,2,3-triazole, 4H-1,2,4-triazole, 2H-tetrazole and 1H-pentazole [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…The enthalpies and Gibbs free energies of formation of the various titled clusters were obtained using Eqs. (11), (12), and (13). Where calculations were performed at STP (T ¼ 298K; P ¼ 1 atm)…”
Section: Bementioning
confidence: 99%
“…All thermodynamic calculations are done at 298.15K and 1atm, considering one mole of complex, by applying Eqs. (8), ( 9), ( 10), ( 11), (12), and (13). The thermodynamics parameters of all studied fragments were calculated with DFT/B3LYP method at 631-G (d) basis, the ΔH f of water at STP is calculated to be -76.384 eV at this level.…”
Section: Thermodynamics Considerationsmentioning
confidence: 99%
See 1 more Smart Citation